2012
DOI: 10.1111/j.1432-2277.2012.01542.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-supplemented drinking water protects cardiac allografts from inflammation-associated deterioration

Abstract: Summary Recent evidence suggests that molecular hydrogen has therapeutic value for disease states that involve inflammation. We hypothesized that drinking hydrogen‐rich water (HW) daily would protect cardiac and aortic allograft recipients from inflammation‐associated deterioration. Heterotopic heart transplantation with short‐course tacrolimus immunosuppression and orthotopic aortic transplantation were performed in allogeneic rat strains. HW was generated either by bubbling hydrogen gas through tap water (Bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…Pure astrocytes (1 × 10 5 /cm 2 ) were divided into four groups: 1) control, cultured with normal medium (NM); 2) HM, cultured with hydrogen‐rich medium (HM); 3) NM + H 2 O 2 , cultured with NM containing 100 μM H 2 O 2 (Sigma) and 15 μM FeCl 2 (Sigma); 4) HM + H 2 O 2 , cultured with HM containing 100 μM H 2 O 2 and 15 μM FeCl 2 after pretreatment of HM for 1 h. The oxidative injury of astrocytes was induced by H 2 O 2 , which can not only permeate cell membranes, but also induce remarkable production of HO• with the existence of ferrous ions (called Feton action). The respective media were changed every 6 h to maintain the concentration of hydrogen at 0.6 mM . Treatments were carried out for 12 h, and then the supernatant or cells were collected for different assays.…”
Section: Meterials and Methodsmentioning
confidence: 99%
“…Pure astrocytes (1 × 10 5 /cm 2 ) were divided into four groups: 1) control, cultured with normal medium (NM); 2) HM, cultured with hydrogen‐rich medium (HM); 3) NM + H 2 O 2 , cultured with NM containing 100 μM H 2 O 2 (Sigma) and 15 μM FeCl 2 (Sigma); 4) HM + H 2 O 2 , cultured with HM containing 100 μM H 2 O 2 and 15 μM FeCl 2 after pretreatment of HM for 1 h. The oxidative injury of astrocytes was induced by H 2 O 2 , which can not only permeate cell membranes, but also induce remarkable production of HO• with the existence of ferrous ions (called Feton action). The respective media were changed every 6 h to maintain the concentration of hydrogen at 0.6 mM . Treatments were carried out for 12 h, and then the supernatant or cells were collected for different assays.…”
Section: Meterials and Methodsmentioning
confidence: 99%
“…Oral intake of HRW is an effective and convenient way to deliver the molecular hydrogen, which is more suitable for application. Some researches showed that oral intake of HRW could protect cardiac allografts from inflammation-associated deterioration, kidney allografts from chronic rejection and so on [27][28][29] . Although the research of hydrogen as a medical therapy has been extensively investigated, its effect on the aspirin-induced gastric mucosal injury has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, many basic studies have demonstrated that H 2 has a role as a novel antioxidant, and it is widely used for preventing and treating various diseases 456. The studies suggest that whether using inhaled H 2 gas or oral H 2 water, H 2 is still an effective method for scavenging reactive oxygen species (ROS) 378…”
Section: Introductionmentioning
confidence: 99%